Gênero crônica: uma proposta de produção textual com estudantes do Ensino Fundamental II a partir da aplicação de uma sequência didática - Ramalho, José Hébio Albuquerque (2019)
The teaching proposals have been committed to the project of training a critical and active human being. Although there have been many advances in reflections on the teaching and learning process, the practice of textual elaboration is still characterized as an activity that remains a major challenge for students and teachers. In this work, therefore, will be presented the process of textual production that was developed with students of a group of 8th grade, from a state public school in Maceió-AL., from the application of a didactic sequence, having as textual genre the chronic one. This pedagogical intervention had as main objective to verify if the texts of the students presented minimal characteristics of this genre. Some grammatical inadequacies Will also be presented in the texts produced by these students. By dealing with text and grammar, it was also necessary, in this work, to develop sections that dealt with both textual genre and grammar (history, concept and reflections). For the development and orientation of this work, we have used theoreticians such as Bagno (2003 and 2007), Possenti (1996 and 2011), Franchi (2006), Neves (2012), Schneuwly and Dolz (2004) and others. As a result, it can be pointed out that the development of the pedagogical activity provided the students with the incentive to practice reading and textual understanding and enabled them to recognize the formal structure of a specific textual genre, as well as contributing to the improvement and development of their abilities of writing, placing them as protagonists in the process of textual production.